A função social da universidade pública com a comunidade do sudeste do Tocantins e nordeste goiano - SILVA, Jéssica da Cunha e (Universidade Federal do Tocantins, 2021)
This study presents the function of the Public University with the Community of the Southeast of Tocantins and Northeast Goiano, being an institution of education, research and extension with the responsibility of transforming the social reality of the residents of the city of Arraias - Tocantins and Region. Given this fact, the objective was to analyze the actions